Pengaruh Informasi Akuntansi Manajemen Dan Sistem Penghargaan Terhadap Kinerja Rumah Sakit (Studi Empiris Pada Rumah Sakit Umum Daerah Arga Makmur) - Diah Khairiyah; Mirra Sri Wahyuni; Herwan MDK; Audry Nurmeliana Putri (UNIVED Press, 2023)
This study aims to determine the effect of: (1) management accounting information on hospital performance (2) reward system on hospital performance (3) management accounting information and reward system simultaneously on hospital performance. The type of research used in this research is quantitative. The population of this study were all employees of the Arga Makmur Regional General Hospital. The sampling technique used in this study was the purposive sampling technique with a total sample of 40 people. Data collection techniques using a questionnaire. The data analysis technique used to answer the hypothesis is multiple regression. Based on the results of the research conducted, it shows that there is an effect of management accounting information and system rewards on Hospital Performance. From the results of the coefficient of determination, it can be seen that the Adjusted R square is 0.442. This shows that management accounting information and reward systems affect hospital performance by 44.2% while the remaining 55.8% can be explained by other factors not examined in this study.